IMPLEMENTATION OF ONLINE LEARNING IN PRODUCTIVE SUBJECTS OF MOTORCYCLE ENGINEERING AND BUSINESS - Noviyana, Kiki; Komaro, Mumu; Noor, Ridwan Adam M.; Ilyasa, Aditya Nur (Universitas Pendidikan Indonesia, 2021)
This study aims to obtain data on the implementation of online learning, obstacles and solutions in productive subjects of Motorcycle Engineering and Business during the Covid-19 pandemic. The research method used is descriptive method. Data collection instruments used observation, interviews, and documentation. The research subjects were 5 students majoring in Motorcycle Engineering and Business. The results of the study indicate that online learning is carried out in accordance with applicable learning standards. Learning is carried out remotely so that learning time is limited, not all the basic competencies in the syllabus are given to students, the internet network is not stable, not all students have smartphones and tools materials for practice at home. The solutions to overcome these obstacles are that schools provide smartphones for students, basic competencies are selected based on the needs in the workshop, use the Whatsapp application for online learning, and teachers make modules so that students can learn independently at home easily. In general, theoretical learning can run well, but practical learning cannot be implemented optimally.